Umorzenie postępowania wykonawczego w sprawach o wykroczenia - Płońska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article discusses the issue of discontinuation of enforcement proceedings in petty offense cases. In Article 15(1) of the Executive Penal Code, the legislator defined three negative conditions for enforcement proceedings. Two of them was indicated clearly: the death of the convicted person (punished in petty offense proceedings) and the limitation for the execution of the penalty. The third condition was vaguely defined as “other reasons excluding this procedure”. The article aims to analyze said grounds for the obligatory discontinuation of enforcement proceedings, taking into account the views of the doctrine and jurisprudence.
Keywords: discontinuation of enforcement proceedings; petty offense law; limitation period for enforcement; death of the convicted person; other reasons excluding enforcement proceedings